How to Safeguard Subsidiarity and Competition in the European Union - Bernholz, Peter; Justus Liebig University Giessen (My University, 2009)
The assignment of rights to as low political levels as possible recommends itself because preferences of citizens are better known at the communal, provincial or state level, because their influence is greater, political powers are more distributed and since decentralization furthers efficiency and innovation in a system. Thus subsidiarity requires that only the necessary framework and those decisions related to cases with strong externalities or to public goods covering the whole society are taken at the highest level. Looking from this perspective at the Lisbon Treaty proposed for the European Community several important shortcomings are found which are mainly related to the fields of overlapping competencies of the Union and the member states. It is shown that the principle of subsidiarity, which has to be safeguarded by introducing adequate institutions, would be much better served by the proposals of the European Constitutional Group.
Keywords: ddc:100; ddc:330